Site-specific Phosphorylation of Kindlin-3 Protein Regulates Its Capacity to Control Cellular Responses Mediated by Integrin α(IIb)β(3) - Bialkowska, Katarzyna (J Biol Chem, 2015)
The contributions of integrins to cellular responses depend upon their activation, which is regulated by binding of proteins to their cytoplasmic tails. Kindlins are integrin cytoplasmic tail binding partners and are essential for optimal integrin activation, and kindlin-3 fulfills this role in hematopoietic cells. Here, we used human platelets and human erythroleukemia (HEL) cells, which express integrin α(IIb)β(3), to investigate whether phosphorylation of kindlin-3 regulates integrin activation. When HEL cells were stimulated with thrombopoietin or phorbol 12-myristate 13-acetate (PMA), α(IIb)β(3) became activated as evidenced by binding of an activation-specific monoclonal antibody and soluble fibrinogen, adherence and spreading on fibrinogen, colocalization of β(3) integrin and kindlin-3 in focal adhesions, and enhanced β(3) integrin-kindlin-3 association in immunoprecipitates. Kindlin-3 knockdown impaired adhesion and spreading on fibrinogen. Stimulation of HEL cells with agonists significantly increased kindlin-3 phosphorylation as detected by mass spectrometric sequencing. Thr(482) or Ser(484) was identified as a phosphorylation site, which resides in a sequence not conserved in kindlin-1 or kindlin-2. These same residues were phosphorylated in kindlin-3 when platelets were stimulated with thrombin. When expressed in HEL cells, T482A/S484A kindlin-3 decreased soluble ligand binding and cell spreading on fibrinogen compared with wild-type kindlin-3. A membrane-permeable peptide containing residues 476–485 of kindlin-3 was introduced into HEL cells and platelets; adhesion and spreading of both cell types were blunted compared with a scrambled control peptide. These data identify a role of kindlin-3 phosphorylation in integrin β(3) activation and provide a basis for functional differences between kindlin-3 and the two other kindlin paralogs.